In vivo and protease-activated receptor-1-mediated platelet activation but not response to antiplatelet therapy predict two-year outcomes after peripheral angioplasty with stent implantation - Gremmel, Thomas; Steiner, Sabine; Seidinger, Daniela; Koppensteiner, Renate; Panzer, Simon; Kopp, Christoph W. (Thrombosis and Haemostasis, 2014)
Data linking the response to antiplatelet therapy with clinical outcomes after angioplasty and stenting for lower extremity artery disease (LEAD) are scarce. Moreover, associations of in vivo and thrombin-inducible platelet activation with the occurrence of adverse events have not been investigated in these patients, so far. We therefore assessed clinical outcomes and on-treatment platelet reactivity by four test systems in 108 patients receiving dual antiplatelet therapy after infrainguinal angioplasty and stenting for LEAD. Further, in vivo and thrombin receptor-activating peptide (TRAP)-6-inducible glycoprotein (GP) IIb/IIIa activation and P-selectin expression were measured as sensitive parameters of platelet activation. The primary endpoint was defined as the composite of atherothrombotic events and target vessel restenosis or reocclusion. Residual platelet reactivity to adenosine diphosphate and arachidonic acid was similar between patients without and with adverse outcomes within two-year follow-up (all p>0.05). Further, the occurrence of clinical endpoints did not differ significantly between patients without and with high on-treatment residual platelet reactivity by all test systems (all p>0.05). In contrast, in vivo and TRAP-6-inducible platelet activation were significantly more pronounced in patients with subsequent adverse events (all p<0.05), and high levels of platelet activation were independent predictors of the primary endpoint (adjusted hazard ratios: 3.5 for high in vivo activated GPIIb/IIIa, 2.9 for high TRAP-6-inducible activated GPIIb/IIIa, 2.3 for high in vivo P-selectin, and 3 for high TRAP-6-inducible P-selectin; all p<0.05). In conclusion, in vivo and protease-activated receptor-1-mediated platelet activation predict two-year clinical outcomes in stable patients undergoing angioplasty and stenting for LEAD.
Keywords: Peripheral arterial disease; angioplasty; stenting; platelet reactivity